Nurses' preparedness to care for women exposed to Intimate Partner Violence: a quantitative study in primary health care - Sundborg Eva M; Saleh-Stattin Nouha; Wändell Per; Törnkvist Lena (BMC, 2012)
Abstract Background Intimate partner violence (IPV) has a deep impact on women's health. Nurses working in primary health care need to be prepared to identify victims and offer appropriate interventions, since IPV is often seen in primary health care. The aim of the study was to assess nurses' preparedness to identify and provide nursing care to women exposed to IPV who attend primary health care. Method Data was collected using a questionnaire to nurses at the primary health care centres. The response rate was 69.3%. Logistic regression analysis was used to test relationships among variables. Results Shortcomings were found regarding preparedness among nurses. They lacked organisational support e.g. guidelines, collaboration with others and knowledge regarding the extensiveness of IPV. Only half of them always asked women about violence and mostly when a woman was physically injured. They felt difficulties to know how to ask and if they identified violence they mostly offered the women a doctor's appointment. Feeling prepared was connected to obtaining knowledge by themselves and also to identifying women exposed to IPV. Conclusion The majority of the nurses were found to be quiet unprepared to provide nursing care to women exposed to IPV. Consequences might be treatment of symptoms but unidentified abuse and more and unnecessary suffering for these women. Improvements are needed on both at the level of the organisation and individual.